Strategi Pengendalian Kebakaran Hutan dan Lahan Di IUPHHK-HT PT Finnantara Intiga Provinsi Kalimantan Barat - Bambang Hero Saharjo; Robi Deslia Waldi (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2019)
The forest fire control is done through prevention, suppression, and following fire activities at national level and forest unit level. This research was divided in to informan and responden subjects. The implementation strategy of forest fire control in PT Finnantara Intiga adapted from PP Numb. 4 year 2001 about controling damaged forest and or environment pollution that related to forest fire and or land according the provision of article 20 (1) PP Numb. 45 year 2004 about forest protection that declare to prevent and limiting the destruction of forest caused by forest fire, and need to do controling of forest and land fire. The majority of people work as a farmer that have time schedule of land cultivation. The event of forest fire and land in the its highest level that occurs in august to september because in that time most of farmer doing fields burning with average of total extent about 25.8 hectares and the amount of hotspots were about 144 point in the period of 2010 to 2015.Keywords: Stretgy, fire prevention control, hotspot